Description of the pupa and redescription of the third instar of Phileurus valgus (Olivier) (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) - Ibarra-Polesel, Mario G.; Valle, Nestor G.; Neita-Moreno, Jhon C.; Damborsky, Miryam P. (Zootaxa, 2017)
Phileurus valgus (Olivier) (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) is a common species widely distributed from the southern United States to Argentina and the West Indies. In this work the immature stages are described and illustrated based on specimens from Argentina. A key to the known third-stage larvae of New World Phileurini species is provided and updated. Notes on the life cycle and natural history are also included.